EFEKTIVITAS EKSTRAK BIJI PEPAYA (Carica papaya) TERHADAP KESEMBUHAN DAN KELANGSUNGAN HIDUP IKAN JELAWAT (Leptobarbus hoevenii) YANG DIINFEKSI BAKTERI Aeromonas hydrophila - Rahayu, Endang; Dewantoro, Eko; Farida, Farida; Hadiarti, Dini (Jurnal Ruaya : Jurnal Penelitian dan Kajian Ilmu Perikanan dan Kelautan, 2023)
Jelawat fish (Leptobarbus hoevenii) are found in several rivers in Kalimantan and Sumatra. Often encountered obstacles in fish farming is the bacterial disease Aeromonas hydrophila, known as Motile Aeromonas Septicemia (MAS). Treatment of disease can use natural ingredients that function as antimicrobials. Papaya seeds contain antimicrobials; besides that, they also contain secondary metabolites such as phenols, terpenoids, alkaloids, and saponins. The terpenoid group is the main component of papaya seeds and has antibacterial activity. This study aims to determine the effectiveness of the best papaya seed extract on the survival of jelawat fish infected with Aeromonas hydrophila bacteria. The treatment in this study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments were treatment A (soaking with papaya seed extract at 0 ppm), treatment B (soaking with papaya seed extract at 40 ppm), treatment C (soaking with papaya seed extract at 80 ppm), and treatment D (soaking with papaya seed extract at 120 ppm). The results showed that the administration of papaya seed extract by immersion had a significant effect on the response to high feeding, with an average absolute weight growth value of 1.33 grams, a 100% survival rate, and wound healing in sharks infected with A. hydrophila bacteria starting to normalize or heal. Meanwhile, the water quality observed during the study was quite supportive for the survival of the jelawat, with temperatures ranging from 27–28, dissolved oxygen (DO) ranging from 7-8.7 mg/L, pH ranging from 6.5 to 7.3, and ammonia values from 0.1–0.3 mg/L. Giving 80 ppm through soaking papaya seed extract with jelawat fish is the best.